A terahertz-vibration to terahertz-radiation converter based on gold nanoobjects: a feasibility study - Moldosanov, Kamil; Postnikov, Andrei (Beilstein Journal of Nanotechnology, 2016)
Background: The need for practical and adaptable terahertz sources is apparent in the areas of application such as early cancer diagnostics, nondestructive inspection of pharmaceutical tablets, visualization of concealed objects. We outline the operation principle and suggest the design of a simple appliance for generating terahertz radiation by a system of nanoobjects – gold nanobars (GNBs) or nanorings (GNRs) – irradiated by microwaves.Results: Our estimations confirm a feasibility of the idea that GNBs and GNRs irradiated by microwaves could become terahertz emitters with photon energies within the full width at half maximum of the longitudinal acoustic phononic DOS of gold (ca. 16–19 meV, i.e., 3.9–4.6 THz). A scheme of the terahertz radiation source is suggested based on the domestic microwave oven irradiating a substrate with multiple deposited GNBs or GNRs.Conclusion: The size of a nanoobject for optimal conversion is estimated to be approx. 3 nm (thickness) by approx. 100 nm (length of GNB, or along the GNR). This detailed prediction is open to experimental verification. An impact is expected onto further studies of interplay between atomic vibrations and electromagnetic waves in nanoobjects.
Keywords: longitudinal acoustic phonon; microwave photon; nanobar; nanoring; terahertz emitter

Fundamental and Applied Nano-Electromagnetics - Postnikov, A.; Moldosanov, K. (Phonon-Assisted Radiofrequency Absorption by Gold Nanoparticles Resulting in Hyperthermia, 2016)
Proceedings of the NATO Advanced Research Workshop on Fundamental and Applied Electromagnetics, Minsk, Belarus, May 25–27, 2015. Preprint: http://arxiv.org/abs/1508.00735

(untitled) - Muñoz, J. A.; Lucas, M. S.; Mauger, L.; Halevy, I.; Horwath, J.; Semiatin, S. L.; Xiao, Y.; Chow, P.; Stone, M. B.; Abernathy, D. L.; Fultz, B. (Phys. Rev. B, 2013)

(untitled) - Bayle, M.; Combe, N.; Sangeetha, N. M.; Viau, G.; Carles, R. (Nanoscale, 2014)

(untitled) - Lynn, J. W.; Smith, H. G.; Nicklow, R. M. (Phys. Rev. B, 1973)

Solid State Physics - Ashcroft, N. W.; Mermin, N. D. (Saunders College, 1976)

(untitled) - Kubo, R. (J. Phys. Soc. Jpn., 1962)

(untitled) - Kubo, R. (J. Phys. Colloques, 1977)

(untitled) - Singh, R. N.; Ali, I. (Int. J. Appl. Phys. Math., 2013)

(untitled) - Sauceda, H. E.; Garzón, I. L. (J. Phys. Chem. C, 2015)

(untitled) - Dal Corso, A. (J. Phys.: Condens. Matter, 2013)

(untitled) - Postnikov, A. V.; Moldosanov, K. A. (J. Nanophotonics, 2012)

(untitled) - Vieu, C.; Carcenac, F.; Pépin, A.; Chen, Y.; Mejias, M.; Lebib, A.; Manin-Ferlazzo, L.; Couraud, L.; Launois, H. (Appl. Surf. Sci., 2000)

(untitled) - Fukuoka, A.; Araki, H.; Sakamoto, Y.; Sugimoto, N.; Tsukada, H.; Kumai, Y.; Akimoto, Y.; Ichikawa, M. (Nano Lett., 2002)

(untitled) - Pazos-Pérez, N.; Baranov, D.; Irsen, S.; Hilgendorff, M.; Liz-Marzán, L. M.; Giersig, M. (Langmuir, 2008)

(untitled) - Xiang, C.; Kung, S.-C.; Taggart, D. K.; Yang, F.; Thompson, M. A.; Güell, A. G.; Yang, Y.; Penner, R. M. (ACS Nano, 2008)

(untitled) - Tseng, H.-Y.; Lee, C.-K.; Wu, S.-Y.; Chi, T.-T.; Yang, K.-M.; Wang, J.-Y.; Kiang, Y.-W.; Yang, C. C.; Tsai, M.-T.; Wu, Y.-C.; Chou, H.-Y. E.; Chiang, C.-P. (Nanotechnology, 2010)

(untitled) - Budaev, B. V.; Bogy, D. B. (J. Appl. Phys., 2015)

(untitled) - Chiloyan, V.; Garg, J.; Esfarjani, K.; Chen, G. (Nat. Commun., 2015)

(untitled) - Beardsley, R. P.; Akimov, A. V.; Henini, M.; Kent, A. J. (Phys. Rev. Lett., 2010)

(untitled) - Riedinger, R.; Hong, S.; Norte, R. A.; Slater, J. A.; Shang, J.; Krause, A. G.; Anant, V.; Aspelmeyer, M.; Gröblacher, S. (Nature, 2016)

(untitled) - Stannigel, K.; Rabl, P.; Sørensen, A. S.; Zoller, P.; Lukin, M. D. (Phys. Rev. Lett., 2010)

(untitled) - Stannigel, K.; Rabl, P.; Sørensen, A. S.; Lukin, M. D.; Zoller, P. (Phys. Rev. A, 2011)